Anatomy of the vasculature of the lower leg and harvest of a fibular flap: a systematic review. Issue 9 (November 2017) - Abou-Foul, A.K.; Fasanmade, A.; Prabhu, S.; Borumandi, F.
Abstract: The fibular free flap (FFF) is based on the peroneal artery, which has a consistent anatomy and makes a minimal contribution to the pedal circulation. However, certain anatomical variations in the vasculature of the leg might leave the peroneal artery with a major role in the perfusion of the foot, and to raise a FFF could lead to ischaemic complications. Our aim was to review the implications of anatomical variants on planning and harvest of a FFF. We systematically reviewed all relevant publications, and included 28 cases that described a dominant peroneal artery and FFF. Most of the patients had clinically normal pulses, and the dominant peroneal artery was diagnosed by preoperative vascular mapping. Variants of the peronea arteria magna were the most common. Bilateral anatomical variations were reported in 10 cases. The surgical plan to harvest the fibula was altered in 21 patients with vascular aberrations. In 17 of the 21, the leg with the anatomical variant was not used. The opposite fibula was used in 10 cases. In four of the 21, the FFF was harvested from the leg with a dominant peroneal artery, after the technique of harvest had been modified. The FFF was successfully harvested without any modification in only five cases. Two patients who had not had preoperative vascular mapping developed acute ischaemia of the limb after harvest of the FFF because of an existing peronea arteria magna. Preoperative vascular mapping is a valuable way to assess that perfusion of the foot is adequate, and it provides accurate information about the vascular anatomy, cutaneous perforators, and the fibular blood supply, with minimal or no added cost or risks.